1985
DOI: 10.1115/1.3261099
|View full text |Cite
|
Sign up to set email alerts
|

The Leading-Edge-Groove Tilting-Pad Thrust Bearing: Recent Developments

Abstract: This paper compares the leading edge groove and pressurized supply (flooded) lubricant supply methods, and analyzes their influence on the performance of equalizing tilting pad thrust bearings. This paper presents new experimental data on 6-shoe, 267 mm (10 1/2 in.) O.D. bearings, operating at shaft speeds up to 14000 rpm, with loads ranging up to 3.45 MPa (500 psi) for two different lubricants. The data presented details the power loss and babbitt temperature performance of two versions of the leading-edge-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…This measure allows up to 70 per cent reduction in power loss [15] and up to 20 K reduction in temperature [12,13], depending on operating conditions and the system used. In the present study a smaller reduction in energy consumption is achieved and only before the onset of turbulence.…”
Section: Discussionmentioning
confidence: 99%
“…This measure allows up to 70 per cent reduction in power loss [15] and up to 20 K reduction in temperature [12,13], depending on operating conditions and the system used. In the present study a smaller reduction in energy consumption is achieved and only before the onset of turbulence.…”
Section: Discussionmentioning
confidence: 99%
“…The performance data presented isolates and identifies the individual contributions of shoe pivot location and oil supply method. These issues were raised in the discussion of the .vo previous papers [1,2], and based on this test data, should now be resolved.…”
Section: Introductionmentioning
confidence: 87%
“…Cool, undiluted lubricant is introduced from this groove directly into the fluid film of each shoe. This method of supplying oil into the hydrodynamic wedge has been found to significantly reduce bearing frictional power losses and babbitt temperatures [1,2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, he has shown that the LEG design of thrust pad will perform satisfactorily, when running backwards under heavily loaded conditions. Horner et al 2 unidirectional do not preclude occasional successful bidirectional operation.…”
Section: K Brockwellmentioning
confidence: 95%